Management of Symptomatic Renal Cysts by Laparoscopy: Our Initial Experience (Bangladesh Journal of Urology, 2020)
Introduction and objective: Over the last decade laparoscopic surgery has been popularized and developed to such an extent that it can be considered gold standard for many types of procedures in urology. Currently the majority of operations in urologic field can be performed by laparoscopy. This is because it is as effective as open surgery, but associated with less postoperative pain, shorter hospital stay, faster recovery and has better cosmetic result. The aim of the study is to evaluate the results of our experience of treating symptomatic renal cysts by laparoscopy.Materials and methods: This prospective study was conducted from January 2015 to December 2017 in the Department of Urology in a single unit of Dhaka Medical College Hospital. All the patients were admitted through out-patient department. Among them those who fulfilled the criteria were selected for laparoscopic surgery. All patients were diagnosed by ultrasonography and computed tomography to determine the Bosniak classification of the cyst & informed written consent was taken. Total five laparoscopic decortication of renal cysts were performed and the results of our experience were compared with data from published article. Pain and cyst recurrence were assessed during the follow-up.Results: Our study described the results of 05 laparoscopic decortication of renal cysts. All procedures were completed successfully by transperitoneal approach, with no major intraoperative and postoperative complications. There was a placement of drain tube in one patient. The mean (range) operative duration was 68 (40–110) min, affected by the site and number of cysts decorticated. The mean post operative hospital stay was 1.8 (1- 3) days. All patients were symptom-free and no sign of recurrence during the follow-up.Conclusion: Laparoscopic decortication of symptomatic renal cysts should be the standard of care and it is feasible with conventional laparoscopic instruments and gives a better cosmetic outcome.Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.137-139